Right ventricle inflow obstructing mass proven to be a synovial sarcoma - Seo, Guang-Won (Pioneer Bioscience Publishing Company, 2014)
Soft tissue sarcoma is the most common malignant cardiac tumor. The chief modes of presentation are embolization, obstruction, and arrhythmogenesis. We describe an unusual case of a 27-year-old man who presented with nausea and dyspnea on exertion. Transthoracic echocardiography and computed tomography revealed a huge mass in the right heart that extended through the inferior vena cava and right renal vein to the right kidney. The cardiac mass was resected, and an immunohistochemical analysis revealed it to be a TLE1-positive synovial sarcoma. After surgery, the patient received serial adjuvant chemotherapy. We herein describe the case with a brief review.